‘They had lived for nothing in this world’: Linguistic and socio-demographic considerations on a historically stigmatised marital status - Savu, Adriana (Adult Education Discourses, 2022)
Existence outside of marriage associated, especially in the case of women, with the lack of children carries an almost universal stigma. It has historically been perceived as a violation of social norms and a danger to local communities and states. In the latest couple of decades, a growing number of studies focused on the stereotypes and stigma of singlehood, but not many of them addressed the issues of stereotype formation and the etiology of stigma related to never-married people. This paper explores the relationship between Romanian terms referring to never-married people and the local socio-demographic context from a historical perspective. It also makes a few cultural-comparative remarks to show that, as it is said, language mirrors culture and society. The number and the linguistic form of the available words for men and women who did not marry reflect society’s concerns at one point in time or another. The way the language is used affects the persistence of category representation and the consensualisation of stereotypes. Finally, this paper supports the idea that historical, multidisciplinary and comparative approaches provide a better understanding of social and cultural realities.